Inhibition of ERO1a and IDO1 improves dendritic cell infiltration into pancreatic ductal adenocarcinoma - Tay, Apple Hui Min; Cinotti, Riccardo; Sze, Newman Sui Kwan; Lundqvist, Andreas (Frontiers in Immunology, 2023)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal and treatment resistant cancers. Due to its desmoplastic and hypoxic nature along with an abundance of myeloid cell infiltration and scarce T cell infiltration, PDAC is considered a cold tumor. Here we sought to investigate myeloid cell infiltration and composition in PDAC spheroids by targeting the hypoxia-associated pathways endoplasmic reticulum oxidoreductase 1 alpha (ERO1a) and indoleamine 2,3-dioxygenase 1 (IDO1). Inhibition of ERO1a and IDO1 significantly improved monocyte infiltration and differentiation into dendritic cells. LC-MS/MS analysis of the PDAC spheroid secretome identified downregulation of hypoxia and PDAC pathways, and upregulation of antigen presentation pathways upon inhibition of ERO1a and IDO1. Furthermore, immunomodulatory factors involved in immune infiltration and migration including interleukin-8, lymphocyte cytosolic protein 1, and transgelin-2, were upregulated upon inhibition of ERO1a and IDO1. Collectively, our results show that inhibition of ERO1a and IDO1 modulates the tumor microenvironment associated with improved monocyte infiltration and differentiation into dendritic cells to potentially influence therapeutic responses in patients with PDAC.